An Interactive Mobile Application for Gardening Education and Community Empowerment Developed Using the Waterfall Method - Desepta Isna Ulumi; Anggi Perwitasi; Clara Oxana Azalia; Anaqah Aisyah Hadiasmah; Requestha Amorine Montass (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Indonesia is currently facing a food crisis exacerbated by climate change, which disrupts agricultural patterns and causes crop failures. These disruptions lead to increased food prices and reduced purchasing power, particularly affecting the lower-income population. One sustainable solution is home gardening, which can enhance food availability and reduce household expenses. However, not everyone has the knowledge or resources to start gardening. To address this gap, the PANENKU application was developed as a mobile-based platform aimed at educating users on how to grow essential food crops such as chilies, shallots, and ginger. PANENKU integrates interactive learning through simulation games that guide users step-by-step, from planting to harvesting. The application leverages the Waterfall development model for systematic design and includes features such as AR (Augmented Reality) experiences, informative articles, and a community forum. These elements foster engagement, support peer-to-peer learning, and enhance users gardening knowledge. By incorporating educational gameplay and expert interaction, PANENKU not only supports individual self-sufficiency but also promotes environmental sustainability and strengthens local economies. System testing using black box testing which tests four features shows that the features can run well and the System Usability Scale (SUS) shows a result of 86%. The results of this test show that the app is particularly beneficial for housewives and beginner gardeners, offering an innovative and accessible approach to addressing food security challenges in Indonesia. Ultimately, PANENKU aspires to be a positive, inclusive platform for agricultural education and community empowerment.